Dynamic modeling and robust nonlinear control of unmanned quadrotor vehicle - Elhennawy, Amr (AUC Knowledge Fountain, 2018)
It is not easy to control a quadrotor due to its highly nonlinear dynamics, variable coupling and model uncertainties. The underactuation property of the quadrotor also poses another degree of complexity to the model due to the limited availability of control techniques that can be applied to underactuated systems. This thesis presents the development of mathematical modeling, control techniques, simulation and real-time testing on a developed quadrotor as an unmanned aerial vehicle. Modeling of the dynamic system of a quadrotor including the motor dynamics is carried out using Newton-Euler mechanics and state space representation is obtained. Using this model a second-order Sliding Mode Control (SMC) is developed as a nonlinear robust control technique. For the SMC development, quadrotor system is divided into two subsystems, one represents the fully actuated degrees of freedom and the other one represents the underactuated degrees of freedom. The aim of the proposed ight controller is to achieve asymptotic position and attitude tracking of the two subsystems by driving the tracking errors to zero to achieve the required tracking performance. Tackling of chattering problem associated with SMC is introduced. Using the developed mathematical model and the developed two control techniques as linear and nonlinear approaches: the Proportional plus Derivative (PD), and SMC, simulation testing is conducted with and without the presence of external disturbances representing weight variation. Multiple simulations testing are performed to ensure the adequacy of the proposed control techniques using MATLAB and Simulink. Detailed discussion on the results of each control technique and comparison are presented with elaborate consideration of the robustness against weight variation. The simulation results demonstrate the ability of the SMC to drive the vehicle to stability and achieve the desired performance characteristics. . Finally, hardware design of a quadrotor has been developed and implemented with considerations on the hardware challenges are presented. Results of real-time ght tests using the two developed control techniques are presented and compared with that of the simulation results and it shows reliable performance of the nonlinear robust SMC controller. Flight tests results came consistent with the simulation results in terms of tracking performance, robustness and actuators e orts. Hardships in the implementation are mentioned and recommendations and future work are proposed. .